2019
DOI: 10.3390/medicina55080490
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Effusion and Its Current Management: A Review

Abstract: Malignant pleural effusion (MPE) is an exudative effusion with malignant cells. MPE is a common symptom and accompanying manifestation of metastatic disease. It affects up to 15% of all patients with cancer and is the most common in lung, breast cancer, lymphoma, gynecological malignancies and malignant mesothelioma. In the last year, many studies were performed focusing on the pathophysiological mechanisms of MPE. With the advancement in molecular techniques, the importance of tumor-host cell interactions is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 82 publications
(158 reference statements)
2
79
0
6
Order By: Relevance
“…Only two cases had insufficient material for analysis, reinforcing the advantage of liquid‐based preparations, which provide additional material for these tests, without compromising DNA viability or affecting test results 2 . Often, in a metastatic context, cytology specimens are the only tumor samples available for researching these genetic alterations 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Only two cases had insufficient material for analysis, reinforcing the advantage of liquid‐based preparations, which provide additional material for these tests, without compromising DNA viability or affecting test results 2 . Often, in a metastatic context, cytology specimens are the only tumor samples available for researching these genetic alterations 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells in patients with advanced lung cancer infiltrate pleural cavity via the hematogenous, direct, or lymphatic spread, resulting impaired lymphatic drainage and pleural effusion accumulation. 24 Cytological examination of pleural effusion showed that 95% of malignant serous effusions represented metastatic disease, mainly composed of adenocarcinomas (70%-77%). 25 In this study, 88.3% of the enrolled patients with lung adenocarcinoma and 81.8% of the patients with local or distant metastases, two characteristics that were similar to those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…26 Molecular testing based on pleural effusion cytology specimens has been widely recommended in clinical guidelines of NSCLC and has become a routine method used in clinical practice. 24,27,28 The mutation detection rates based on this kind of specimens are affected by tumor content. 21,22 Previous studies showed that pleural effusion supernatants contain more abundant tumor derived DNA (ctDNA) than pleural effusion sediments and plasma samples, and had higher detection rate of EGFR driver mutations especially for detection of T790M in EGFR-TKI relapsed patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant pleural effusion (MPE) is a type of pleural effusion characterized by the transfer of malignant cells to the pleura or other causes of pleural effusion (1). MPE is a common complication of malignant tumors, with an incidence of 15% in cancer patients (2,3), which usually indicates that the disease has reached the advanced stage, and is associated with high morbidity and mortality, along with reduced treatment options. MPE is most commonly found in lung cancer, followed by breast cancer (4), with the common symptoms being dyspnea, cough, and chest pain.…”
Section: Introductionmentioning
confidence: 99%